Commodification of Local Culture in the Development of Wayang Tourism Villages - Hidayati, Al Fida; Siregar, Yuanita Aprilandini (Universitas Pattimura, 2024)
This study explores the commodification of local culture in the development of Kepuhsari as a Wayang-themed tourism village. The objective is to identify the internal and external factors that drive the integration of local cultural assets, particularly wayang kulit (shadow puppetry), into tourism development, as well as to analyze the processes through which commodification occurs. Employing a qualitative research approach, data were collected through direct observations and in-depth interviews with community members and stakeholders. The findings reveal that internal factors such as the community’s modern mindset, the presence of cultural resources, economic aspirations, cultural preservation efforts, and local creativity are pivotal in shaping tourism development. Externally, market demands, consumer preferences, and institutional support play significant roles. The commodification of wayang manifests through functional and aesthetic transformations, including changes in performance context, design, production methods, and consumption patterns. Once a ritual medium used in ruwatan ceremonies, wayang has been adapted into customizable tourism products that cater to visitor interests and educational values. This study offers a nuanced understanding of how traditional cultural forms are recontextualized within the tourism economy, highlighting both opportunities and risks in balancing cultural preservation with economic objectives. The novelty of this research lies in its focused examination of cultural commodification at the micro-community level, providing theoretical and practical insights for future studies in cultural studies, tourism development, and socio-economic anthropology. It recommends a more ethical and participatory model of tourism that respects cultural integrity while fostering local economic resilience.